The role of the national curriculum in shaping natural concepts in the primary grades - Hamrayeva Muhayyo Erkin qizi (Peerian Journals Publishing, 2022)
This article discusses the methods of forming concepts of nature in the primary school in the framework of the national curriculum, explaining their specificity
Keywords: framework; forming; specificity; primary